Ecopolítica: derivas do espaço sideral - Siqueira, Leandro Alberto de Paiva (2015)
Beginning with the second half of the twentieth century, rockets, satellites, probes, spacecraft, and space stations have allowed for the occupation of Earth's orbit and achievement of space travel to nearby locations to Earth. Driven by the arms race, space technology projected war and politics into orbit, establishing the first planetary monitoring systems, initially used to spy on missiles. Interested in contemporaneity, this thesis aims to contribute to the study of societies of control showing their outer space proveniences and stressing the importance of the space event for the configuration of exposed power relations belonging to such societies. Besides being taken from its ascendant perspective, in the sense of abandoning the planet, the outer space event should also be analyzed according to its downward movement, in other words, taking into account its drifts, especially the spin-offs that it produces and that can not be reduced to products or socio-economic benefits, but also imply political resizing of the governing of the planet and life. Among the political spin-offs arising from the outer space event we focus on the emergence of the planet-body, which becomes the aim of ecopolitics investment for control societies. The outer space event was decisive to the point that societies of control configured an intelligibility of Earth which understands it as a planet that is fragile when managed. From the administration of state violence to the management of climate change, we present the functioning of a planetary governmentality which seeks to guarantee the safety of transterritorial flows established with the expansion of neoliberalism also on a global scale